Global risk and the dollar - Georgios Georgiadis; Gernot J. Müller; Ben Schumann (European Central Bank (ECB), 2021)
How does global risk impact the world economy? In taking up this question, we focus on the dollar's role in the international adjustment mechanism. First, we rely on high-frequency surprises in the price of gold to identify the effects of global risk shocks in a Bayesian Proxy VAR model. They cause a synchronized contraction of global economic activity and appreciate the dollar. Other key financial indicators adjust in line with pre-dictions of recent theoretical work. Second, we illustrate through counterfactuals that the dollar appreciation amplifies the adverse impact of global risk shocks outside of the US via a financial channel.
Keywords: F31; F42; F44; 330; US dollar exchange rate; global risk shocks; Bayesian proxy structural VAR; minimum relative entropy; counterfactual